An Application of Biometric Security Identification for Automated Teller Machine - Zulkifli, Izyan Fatin Dalila; Fuad, N.; Marwan, M.E. (Open Access Online Journals, 2020)
This project is respectively about implementing an Automated Teller Machine (ATM) by using multimodal biometric identification system, which focuses to retina and fingerprint biometric identification. Instead of using an identification number (PINs) in accessing the ATM transaction performance, biometric identification system had been chosen for safety purpose. In developing this technology, Visual Basic software had been used for a combination of GUI system and implementation of Image Processing system purposes. Personal computer with several software for identification purposes, webcam and fingerprint scanner had been used. Successful identification will allow user to access the ATM transaction performances